Peran Salam Buddhis Dalam Pembiasaan Ucapan Benar (Samma Vaca) Untuk Pembentukan Karakter Buddhis (Studi Kasus Pada Sekolah Minggu Buddha Borobudur Tarakan-Kalimantan Utara) - Cendrani Suwito (Universitas Hamzanwadi, 2026)
This research is based on the habit of using Buddhist greetings within the internal scope of SMB Borobudur. SMB Borobudur students are also taught to speak correctly by the Buddhist Sunday School teachers.. This study aims to find out how the role of Buddhist greetings in the habituation of correct speech (Samma Vaca) which will be the forerunner to the development of Buddhist character at SMB Borobudur Tarakan. This research is a qualitative case study research that uses interview, observation, and documentation methods in collecting data. The sample was selected from SMB Borobudur students and validated with data from SMB Borobudur Buddhist Sunday School teachers, parents of students, and also high school Buddhist teachers who also be a part of SMB Borobudur. The informan are consisted 10 peoples of student, 3 peoples of Buddhist Sunday School teachers, 3 peoples parents of students, and also 1 people of high school Buddhist teachers. From the results of the study, it was found that the Namo Buddhaya greeting did not play a major role in the habit of Samma Vaca for the formation of Buddhist character. The important thing is how the early education begins, namely in the family circle. The habituation process also takes place from an early age, continuously, is closely monitored, and ultimately this is the role of parents who will develop Buddhist character.